Integrated Inbound Marketing Model and Its Impact on Increasing Student Enrollment - Imamah, Istianatul; Mahmudi, Rois; Rofiq, Ainur (Ahlussunnah: Journal of Islamic Education, 2025)
The purpose of this study is to analyze and empirically verify the Integrated Inbound Marketing Model, as well as measure its specific impact on increasing the number of students in educational institutions, as a strategic solution to overcome the inefficiency of traditional marketing methods in the digital era. This research will be conducted at MTs Al-Amiriyyah Darussalam, Indonesia. The approach used in this study is qualitative with a case study research type. The main data collection techniques include in-depth interviews to explore the perspectives and experiences of informants, participant observation. The data analysis technique used is the Three-Flow Interactive Model from Miles and Huberman (data reduction, data presentation, and conclusion drawing). The results of this study show that MTs Al-Amiriyyah Darussalam has developed several special class programs such as the Tahfidz Class and the Academic Strengthening Class (Excellent) which are the main attractions for prospective students, especially students from outside Banyuwangi, the village diniyyah program carried out by students and ustadz MTs Al-Amiriyyah is one of the superior activities that strengthens the relationship between the madrasah and the community around the Islamic boarding school, and the practice teaching and outing class activities carried out by MTs Al-Amiriyyah students in outside schools, partner educational institutions, or religious institutions have a significant impact on increasing the school's digital exposure.